Theories of delinquency : an examination of explanations of delinquent behavior - Shoemaker, Donald J. (New York : Oxford University Press, 1990)
Theories of Delinquency is a comprehensive survey of the theoretical approaches towards understanding delinquent behavior. Donald Shoemaker aptly presents all major individualistic and sociological theories in a standard format with basic assumptions, important concepts, and critical evaluations. Theories covered include biological and psychological explanations, anomie and social disorganization, differential association, drift theory, labeling theory, critical theories, and explanations of female delinquency. Now in its sixth edition, Theories of Delinquency contains up-to-date discussions based on current research throughout, extensive revisions to control theories, especially the general theory of crime, and expanded coverage of integrated and cutting-edge theories. Clearly written, consistently organized, and now thoroughly updated, Theories of Delinquency remains essential reading for advanced undergraduate and graduate students of crime and delinquency"--Provided by publisher.
Includes bibliographical references and indexes.
Keywords: Juvenile delinquency; SOCIAL SCIENCE -- Criminology